Comparison Study of Fabrication and Characterization of Bead Chitosan Hydrogel and Yarn Chitosan Hydrogel From High Molecular Chitosan - Agusnar, Harry (Talenta Publisher, 2020)
The research about comparison study of fabrication and characterization of bead chitosan hydrogel and yarn chitosan hydrogel from high molecular chitosan has been successfully conducted. High molecular chitosan was dissolved into 100 ml of 1, 1.5, and 2% of acetic acid and stirred until the chitosan was dissolved completely. The formed chitosan solution was then taken as much as 6 mL using a syringe and dropped slowly to form small beads into a Petri dish containing NaOH 0.3 M then string into a Petri dish containing acetone 1% and dried at Â±50ÂºC. The bead chitosan hydrogel and yarn chitosan hydrogen results were characterized in which differences of functional groups on chitosan with beads chitosan hydrogel and yarn chitosan hydrogel that occurred in the highest spectra peaks was the band at 3433.29 cm-1, which indicated NH groups on chitosan had changed into an O-H group (3653.18 cm-1) on the bead chitosan hydrogels 1% and yarn chitosan hydrogel 1% which showed the existence of chemical interactions. The yarn chitosan hydrogel has better absorption capability compared to bead chitosan hydrogel. Due to the surface area of the chitosan yarn hydrogel being wider than the beads' chitosan hydrogel.